Global Dynamics, Domestic Coalitions and a Reactive State: Major Policy Shifts in Post-War Turkish Economic Development - Ziya Onis; Fikret Senses (Turkish Economic Association, 2007)
The main objective of this study is to propose an analytical framework to explain the major policy shifts that has characterized post-war Turkish economic development; divided into four phases, starting respectively in 1950, 1960, 1980, and 2001. Its main contribution is to incorporate external and internal factors into this framework within a broadly political economy perspective, attaching particular significance to the role of economic crises in moving from one phase to the other. While the role of external agents is identified as the main factor behind policy shifts, the role of domestic coalitions in support of policy regime in each phase is also recognized. Drawing attention to the role of state in the impressive recent growth of countries such as China, India, and Ireland, the paper argues that there is still room for the state taking on a developmental role. The paper recommends that Turkey follows a similar path by improving state capacity not only with respect to its regulatory role but also in more developmental spheres, encompassing its redistributive and transformative role on the basis of a domestically-determined industrialization strategy.
Keywords: 330; Wirtschaftspolitik; Staatliche Einflussnahme; Wirtschaftskrise; Industrialisierung; Türkei